Mitigating bit-synchronization errors in Huffman-coding-aided index modulation - Liu, Y; Coon, J (Institute of Electrical and Electronics Engineers, 2018)
When utilizing all subcarrier activation patterns (SAPs) in the combinatorial index modulation (IM) scheme, existing techniques either fail to realize the maximum throughput enhancement by using all SAPs or fail to address the bit-level synchronization issue (or error propagation) due to the variablelength nature of the index-domain codebook. To address these drawbacks, we propose using Huffman coding for IM together with two constellation mappings for the bandpass modulation. The proposed scheme induces no signal overhead and is applicable when the index-domain codebook has the maximum encoding rate. Simulations demonstrate the effectiveness of the proposed scheme in mitigating bit-level synchronization errors.